Improved management of species of the African Entandrophragma genus, now listed as vulnerable - (:unkn) unknown (My University, 2019)
Because of the quality of their wood and their many traditional uses, species of the Entandrophragma genus are being intensively logged, and this is likely to compromise their survival unless sustainable management is introduced. This study reviews the current status of the five main commercial Entandrophragma species: Entandrophragma angolense, E. congolense (often confused with E. angolense), E. candollei, E. cylindricum and E. utile. We suggest directions for research to improve sustainable management strategies for this genus. The study draws mainly on published scientific data, economic data (production and export statistics) and on relevant laws and regulations, but also on existing management plans and inventory reports. Although these species are reported as vulnerable on the IUCN Red List, knowledge on their management is still patchy. Industrial and artisanal logging is intensive and does not always follow a validated management plan or abide by the minimum rotation period, both of which would help to ensure the renewal of these resources. Managing them to ensure that logging is sustainable in the long term requires management measures to be developed and complied with. Sustainable use has to be based on appropriate management of natural stands and on reforestation and conservation measures. Research studies to be developed should encompass the growth rates of the species in the light of the changing climate, assessments of stocks (timber, biomass and carbon), updates of their spatial distribution, improvements to natural regeneration, reproduction processes and the anatomical and technical properties of each species. All these research topics are necessary to ensure the permanence of these Entandrophragma species.
Keywords: African Research